Transforming Land Conflicts through a Pentahelix Governance Framework: Lessons from Jambi Province, Indonesia - Muliono, Muliono; Syamsir, Syamsir; Syam, Fauzi; Darminto, Citra (Journal of Governance and Public Policy, 2026)
Land conflict constitutes one of the most prevalent forms of conflict in Jambi and ranks among the most significant agrarian conflicts in Indonesia. Existing land conflict resolution approaches pay limited attention to multi-stakeholder governance. This research aims to examine the dynamics of land conflicts and to explore the application of the pentahelix governance framework in conflict transformation. This study employs a qualitative case study design. The research area is East Tanjung Jabung Regency. This is one of the representative areas of land conflict in Jambi. The research data was obtained through observation, interviews, and focus group discussions. The selection of informants was purposive, and the data were analyzed using thematic analysis to identify key patterns and relationships. The findings reveal that land conflicts possess a complex nature and exert a significant impact on nearly all aspects of the local community. This conflict is intricately linked to the dynamics of political power. In the context of conflict transformation, the pentahelix governance framework provides an effective governance mechanism for transforming land conflicts. Grounded in transformative principles, it promotes multi-stakeholder collaboration through inclusive governance. The framework facilitates collaborative engagement, reshapes stakeholder relationships, and strengthens institutional interactions in complex agrarian conflicts. This study contributes to the development of land conflict resolution strategies by demonstrating the applicability of the pentahelix model, both in Jambi and in broader contexts across Indonesia.